Aid, Paris and the private sector: How to square the circle - Jørgen Estrup (Danish Institute for International Studies (DIIS), 2009)
Support for private sector development is an important item on the ODA budgets of most donor countries and recently, there has even been an upsurge in the weight given to 'private sector led growth'. The paper raises the basic questions: Why inherently commercial activities should actually be supported? Which objectives are pursued in practice and which interventions are appropriate to achieve inclusive and sustainable development? What level of coherence is found between support for private sector development and the principles of the Paris Declaration? In focusing on these issues of 'rationale', 'practice' and 'policy coherence', the analysis finds that according to the development paradigm subscribed to be donors different rationales exist for supporting PSD and based on ideological grounds donors do contest the guiding principles for support. In parallel, however, some donors do directly support private enterprises without concern for a legitimising rationale. Increasingly parts of the donor community has focused on achieving pro-poor growth and sustainable private sector development by implementing the concept of 'making markets work for the poor' (M4P), locally as well as through global value chains. Due to the inherent differences between state and market a hybrid implementation approach is needed, using both public and private modalities and thus colliding with Paris declaration principles of using country systems. Donors have shown little interest in harmonizing their private sector development interventions and the development community has neglected the obvious problems of policy coherence.
Keywords: 330; Entwicklungshilfekonditionen; Kapitalhilfe; Privatwirtschaft; Entwicklungskooperation